Fuzzy Logic-Based Monitoring and Control of Water pH Quality - Genta Fallah Munggaran Sonagar; Fauzi Luqman Noor Ikhwan; Muhammad Rifqi Annaufal (Batrisya Education, 2026)
Water quality monitoring is essential to keep water environmental safety and healthy, espescially when keeping pH levels stable within acceptable standards. Conventional monitoring system usually limited to periodic measurement and lack flexible control mechanism to handle real-time fluctuations. This research based on implementation of a mamdani fuzzy logic-baesd system for continous pH monitoring and autmatic control of water pH quality. With system that integrated to pH sensor with microcontroller to process input data and apply fuzzification, rule assesment, aggregation, and centroid defuzzification. The fuzzy setup classifies pH into acidic, neutral, or basic states and determines appropiate corrective actions acordingly. Experimental testing was conducted under varying pH conditions to evaluate system responsiveness and stabilization performance. This fuzzy method enable adaptable choices, minimizes disruptions from rigid thresholds, and reliably holds pH in target zone.